Missed opportunities for HIV testing persist despite a single educational intervention: how can we close this evidence‐practice gap?. Issue 3 (5th March 2020) - King, Katherine; Seah, Jarrel; Cheng, Allen; Whiting, Sarah; Hoy, Jennifer
Abstract: Background: In Australia, one‐third of human immunodeficiency virus (HIV) diagnoses occur late, with an estimated 11% of people with HIV unaware of their diagnosis. Undiagnosed and untreated HIV infection increases morbidity in the HIV positive person and allows onward transmission of HIV. Aim: To determine the rate of HIV testing in acute general medicine patients with HIV indicator conditions (IC) and evaluate the effectiveness of an educational intervention in improving testing rates. Methods: Single‐centre, tertiary hospital, before‐after study of general medicine inpatients with IC for 12 weeks prior and 10 weeks post an educational intervention focusing on recommendations for HIV testing including IC. The REASON Cohort Discovery Tool was used to search for the IC using ICD‐10 codes and laboratory data. The presence of IC was estimated, and HIV testing rates before and after the intervention were compared. Regression analysis was utilised to identify characteristics associated with HIV testing. Results: Of 1414 admissions in the baseline period and 946 in the post‐period, 161 (11.4%) and 132 (14.0%) had at least one IC present respectively. There were 18 (11.2%) HIV tests performed for admissions with IC in the pre‐period which increased to 27 (20.5%) ( P = 0.028) in the post‐period. Younger patients were more likely to be tested and regression analysis identified the educational intervention (adjusted odds ratio) 2.2 (1.1, 4.4) to be significantly associated with testing. Conclusions: Although HIV testing rates for IC doubled following the intervention, they remained unacceptably low. The recently introduced electronic medical record presents opportunities to prompt HIV testing.